2021
DOI: 10.1021/acs.jpclett.1c01776
|View full text |Cite
|
Sign up to set email alerts
|

Direct Detection and Visualization of the H+ Reaction Process in a VO2 Cathode for Aqueous Zinc-Ion Batteries

Abstract: Because they are safer and less costly than state-of-the-art Li-ion batteries, aqueous zinc-ion batteries (AZIBs) have been attracting more attention in stationary energy storage and industrial energy storage. However, the electrochemical reaction of H+ in all of the cathode materials of AZIBs has been puzzling until now. Herein, highly oriented VO2 monocrystals grown on a Ti current collector (VO2–Ti) were rationally designed as the research model, and such a well-aligned VO2 cathode also displayed excellent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…[8,9] Obstacles to the practical use of zincmetal anodes originate from a relatively negative reduction potential for Zn of −0.762 V versus standard hydrogen electrode (SHE), leading to H 2 evolution and changing the local pH to strong alkaline. [10][11][12] The alkaline environment corrodes the Zn anode via side reactions, leading to poor electrochemical performance including, low Coulombic efficiency (CE) and rapid capacity decay. Additionally, an obstacle is the formation of Zn dendrite and the resulting cell short-circuit.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Obstacles to the practical use of zincmetal anodes originate from a relatively negative reduction potential for Zn of −0.762 V versus standard hydrogen electrode (SHE), leading to H 2 evolution and changing the local pH to strong alkaline. [10][11][12] The alkaline environment corrodes the Zn anode via side reactions, leading to poor electrochemical performance including, low Coulombic efficiency (CE) and rapid capacity decay. Additionally, an obstacle is the formation of Zn dendrite and the resulting cell short-circuit.…”
Section: Introductionmentioning
confidence: 99%
“…However, the proton also has been found to be inserted into the VO 2 -based cathode material. [14] In this case, the H þ ions with a smaller radius and one positive charge than the hydrated zinc ions would greatly enhance ion migration kinetics and maintain structural stability well by reducing the electrostatic force with the host material (Figure 2b). Li et al demonstrated one new reaction mechanism that proton originating from the H 2 O molecules can insert into VO 2 and the Zn 2þ ion reacted with electrolyte to deposit the Zn 4 (OH) 6 SO 4 •5H 2 O at the VO 2 surface to store Zn 2þ ion during the discharge process (Equation ( 4)-( 8)) under the combination of theoretical calculation simulations and in/ex situ characterization (such as XRD, X-ray photoelectron spectroscopy (XPS), and neutron activation analysis (NAA)).…”
Section: Diffusion-controlled Faradaic Processmentioning
confidence: 99%
“…1−3 Aqueous Zn-ion batteries (AZIBs) have gradually received increasing worldwide attention due to straightforward processing, high safety, and environmental friendliness. 4 At present, a number of cathode materials for AZIBs have been developed, including manganese-based compounds, vanadiumbased compounds, Prussian blue analogous, and some other materials. 5 Among various cathode materials, vanadium-based materials have multivalence nature and superior stability of layered structure, presenting a great potential as cathode materials for developing high-performance AZIBs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, electronic products have been integrated into most people’s everyday lives, so the development of renewable and sustainable energy storage systems is necessary. Aqueous Zn-ion batteries (AZIBs) have gradually received increasing worldwide attention due to straightforward processing, high safety, and environmental friendliness . At present, a number of cathode materials for AZIBs have been developed, including manganese-based compounds, vanadium-based compounds, Prussian blue analogous, and some other materials .…”
Section: Introductionmentioning
confidence: 99%